Solidarity and Social Economy and the Question of Territorial Governance: The Case of the Almond Chain Development Program in the Province of Taourirt- East Region (Morocco) - LAKHDARI, Mohammed; AZIACH, Mohamed; ElBAZOUI, Jaouad (Journal of Humanities & Social Sciences, 2024)
The follower of the various interventions out by the actors in the province of Taourirt discovers the great interest that the solidarity and social economy enjoys, most of the projects specifically directed to alleviating unemployment and diversifying sources of income (the councils of the territorial communities, the national initiative for human development, the green Morocco program, international cooperation…) based on the valorization and marketing of soil products, including the almond tree, adapted to the natural environment and local social know-how. However, the evaluation of the outcome of the almond chain development project in the province of Taourirt, which was launched in 2011, still had weak results and did not live up to the aspirations of the local population, which considers diversifying their sources of income and providing job opportunities as the first building block to confront the vulnerability and poverty the suffer from. The issue of poor governance of these interventions – the lack of keeping pace with these projects from processing to production, valuation, and marketing- affects the achievement of the established goals, and the sustainability of these projects collides with the constraints of the climate, especially almonds, which involves farmer and gives priority to the constraints facing the population and the field, will result in positive economic, social and environmental impacts on the image of the Taourirt compared to previous years.